PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA KELAS VII SMP NEGERI 5 MANIAMOLO - Marta, Marta Muliyati Waoma (Universitas Nias Raya, 2024)
Based on the background of the problem, student activity seems to be lacking in the learning process, especially student activity in asking the teacher regarding the material being discussed, students do not understand the material presented, there is a reluctance of students to ask the teacher because they are embarrassed even though they are given the opportunity, but students only listen to the lecture. and do the exercises given. This research aims to determine the influence of the discovery learning model on the learning outcomes of class VII students at SMP Negeri 5 Maniamolo. This type of research is quantitative, descriptive in nature. The population of this research is class VII students, while the sample of this research is students of class VII-A and class VII-B of SMP Negeri 5 Maniamolo. This research data was analyzed using normality tests and hypothesis testing using the SPSS (Statistical product and service solution) application. The results of the two classes, namely the control class and the experimental class, can be said to be more students who have completed learning using the discovery learning model compared to the learning outcomes of students using the conventional learning model and while participating in learning activities using the discovery learning model it appears that in the initial test, students still did not understand the material presented, whereas in the final test after completing the learning process the students really understood what was conveyed by the teacher and were able to get through the assignments given with quite good learning results. Researcher suggestions (1) teachers should use the discovery learning learning model in learning activities because it makes students diligent and think more critically in learning and the attraction gained by studying social studies. (2) Future researchers should carry out this research with a broader scope.